Confided to His Care or Protection: The Late Nineteenth-Century Crime of Workplace Sexual Harassment - McLean, Sara (Columbia Journal of Gender and Law, 1999)
Catherine MacKinnon wrote in 1979, “Sexual harassment, the experience, is becoming ‘sexual harassment, the legal claim.’” In fact, just as the experience of sexual harassment far predated the first sexual harassment claims under Title VII, so, too, did sexual harassment as a claim of legal injury. In recent years, legal historians have begun to examine American law’s early responses to women’s sexual exploitation at work. In a 1996 article, Professor Lea Vandervelde studied the nineteenth-century tort of seduction as a legal claim for sexual harassment. The following year, Professor Jane Larson investigated the campaign to raise state age of consent laws at the end of the nineteenth century, concluding that it sought, in part, to provide women recourse against sexual abuse by employers and by others in positions of authority. Nineteenth-century law addressed the emerging problem of workplace sexual harassment even more directly, however, in a unique state statute that focused particularly on sexual misconduct at work. Beginning in 1879, one state-Missouri-made it a crime for men to “defile… by carnally knowing” the young women “in their care, custody, or employment.” Missouri’s defilement statute provided: If any guardian of any female under the age of eighteen years, or any other person to whose care or protection any such female shall have been confided, shall defile her, by carnally knowing her while she remains in his care, custody, or employment, he shall, in cases not otherwise provided for, be punished by imprisonment in the penitentiary not exceeding five years or by imprisonment in the county jail not exceeding one year and a fine of not less than one hundred dollars. This article will analyze this early sexual harassment statute and the cases under it that reached the Supreme Court of Missouri between 1886 and 1900, at what appears to be the peak of the statute’s application. The article will first briefly explore the underlying shifts in women’s work that occurred over the course of the nineteenth century, as increasing numbers of American women sought work outside their homes, giving rise to new possibilities for women’s sexual independence but also to new threats of women’s sexual abuse, most significantly workplace sexual harassment. The article will next examine the complex ways in which the law reacted to these changes in women’s work, nationally, and then, in Missouri specifically, where the defilement statute formed the most targeted response to the problem of sexual harassment. The article will demonstrate that the defilement statute represented both an extension of the law’s pervasive concern with women’s sexuality and sexual injury and also a retreat from the newly prevailing free labor approach to the master-servant relationship.